PROFIL PENGETAHUAN, SIKAP DAN TINGKAT KONSUMSI MULTIVITAMIN SAAT PANDEMI COVID-19 PADA MAHASISWA FARMASI UMM - Sendi Lia Yunita; Lailatul Khoiriyah; Rizka Novia Atmadani (Universitas Nazhatut Thullab Al- Muafa Sampang, 2022)
Background: The world has experienced the COVID-19 pandemic since the end of 2019. In Indonesia, sourced from Kemenkes RI on March 15, 2021, Indonesians confirmed COVID-19 amounting to 1,425,044 (1.82%). The key to success in fighting COVID-19 is with preventive movements, namely healthy lifestyles and behaviors by wearing masks, washing hands, maintaining distance and increasing the body's immunity to infection. One to maintain immunity with the consumption of nutritious foods and multivitamin consumption. Objectives: To find out the profile of knowledge, attitudes and levels of multivitamin consumption during the COVID-19 pandemic. Method: observational with descriptive analytic surveys using questionnaires, purpose sampling obtained by 93 student. Result: The percentage of respondents about knowledge with good categories was 98.9% (92 people), quite good by 1.1% (1 person) and less good by 0.0%. The percentage of respondents about attitudes with good categories was 80.6% (75 people), the category was quite good by 22.6% (21 people) and less good by 0.0% (0 people). The percentage of respondents about consumption levels with good categories was 80.6% (75 people) and less good at 19.4% (18 people). Conclusion: Have a good knowledge profile, attitude and level of multivitamin consumption in UMM pharmacy students during the COVID-19 pandemic.